Dendrobium rubrostriatum, A New Species of Dendrobium section Aporum from West Kalimantan, Indonesian Borneo - Metusala, Destario; O’byrne, Peter (Phytotaxa, 2020)
Dendrobium rubrostriatum (section Aporum) is described and illustrated from West Kalimantan, Indonesian Borneo. It is morphologically close to Dendrobium lobulatum, but differs in having strongly reflexed petals and dorsal sepal, linear-acute petals, a different shape lateral sepals, a mentum which is only 1.5 times longer than the column, lip that has a straight claw lacking an abrupt bend near the base, a different shape of lobules of mid-lobe, and the disc that has a glabrous callus that in the natural position considerably exceeds the column.